Koch, B.E. (1964): Fossil plants from the Lower Paleocene of the Agatdalen (Angmârtussut) area, central Nûgssuaq peninsula, northwest Greenland - Koch, B. Eske (Meddelelser om Grønland, 1963)
In the present paper fossil plants are described, which are mainly impressions, from a number of localities in the Agatdalen area of the central Nûgssuaq peninsula. All the plants are known to be Early Paleocene in age by means of marine evidence and geological investigations. Their state of preservation and mode of fossilization, their taxonomical position, their frequency and phytogeographical relations, their paleoclimatological and local stratigraphical evidence are discussed. This fossil flora which is designated a MACCLINTOCKIA-METASEQUOIA-CERCIDIPHYLLUM THANATOCOENOSIS is equivalent to the classic Upper Atanikerdluk A flora of HEER, in composition as well as in age, and represents the Arcto-Tertiary flora. It is also synchronous with the Upper Atanikerdluk B flora (HEER). It gives evidence of a warm(?), temperate climate at the time of deposition. Concerning composition an east asiatic element can still be distinguished here at the very threshold to the Tertiary. It contains relic genera from the Cretaceous.